Effect of Weaning Age on Carcass Characteristics of Crossbred Piglets Reared under Intensive System and Slaughtered at 70 Kilogram Body Weight - Montsho, Theresa Theresia; Moreki, John Cassius; Tsopito, Christopher Mareledi; Nsoso, Shalaulani James (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study investigated the effect of weaning age on carcass characteristics of crossbred piglets reared up to 70 kg body weight (BW)  under intensive system. A total of 24 piglets were used in a completely randomized design. The experiment comprised three treatments:  piglets weaned at 21, 28, and 35 days of age with four replicates each with two piglets (castrate and female). At 70 kg BW two piglets  (castrate and female) were randomly selected from each replicate and sacrificed for carcass evaluation. Hot carcass weight (HCW) was  measured and thereafter dressing out percentage was calculated. Carcasses were chilled at 7 0C for 24 hours to determine cold dressed  weight (CDW). Carcasses were cut into the left and right halves along the median line. The left half of the carcass was used to measure  carcass length (CRLTH), average backfat depth and longissimus muscle area (LMA) at the 10th rib, while the right half of the carcass was  physically dissected into bone, muscle and fat and thereafter tissue ratios calculated. Longissimus muscle was removed at the 10th and  11th ribs from the left half of the carcass for chemical composition analysis. Data were analysed using General Linear Model. Weaning  age had no influence (p >0.05) on HCW, dressing percentage, CDW, CRLTH, average backfat thickness, average backfat depth, LMA and  carcass lean percentage. No significant differences (p >0.05) were observed on average percentages of bone, muscle and fat tissue and  their tissue ratios. Weaning age did not influence (p >0.05) moisture, protein, fat and ash contents of the meat. In addition, weaning  age had no (p >0.05) effect on carcass characteristics, physical and chemical body composition of meat. These results indicate that  piglets can be weaned at 21, 28 and 35 days of age without detrimental effects on carcass characteristics, physical and chemical body  composition of pork.
Keywords: Carcass characteristics; Chemical body composition; Pigs; Weaning age; Physical body composition